(untitled) (Computer-Assisted Language Learning Electronic Journal, 2024)
Notwithstanding the widespread use of technology in everyday life, there is scant empirical evidence of its impact on students’ academic learning, particularly in EFL settings. This study sought to determine the impact of a digital game-based student response system called Kahoot on students’ English language learning at a Chilean vocational higher-education EFL classroom. To this end, a pretest-posttest quasi-experimental study was set up. A survey was also administered to explore students’ perceptions of and attitudes towards the use of Kahoot in the EFL classroom. The results of the quasi-experiment showed a statistically significant difference in scores of a low-stakes test for students who used Kahoot versus students who did not. Additionally, the results from the survey indicated that students’ perceptions of and attitudes towards the use of Kahoot were found to be highly positive, which contributed to creating a better classroom environment and fostered a better academic performance.